Intermediate quantum mechanics - Bethe Hans A; Jackiw Roman (Kolkata Levant Books, 2005)
This revised edition is mainly of pedagogical nature. It provides the brief description of recent progress in the treatment of electron correlations. These new developments based on the Bruckner Bethe Goldstone method in nuclear physics help substantially
Keywords: Quantum mechanics